Structural characterization of PEGylated polyethylenimine-entrapped gold nanoparticles: an NMR study. Issue 18 (30th June 2016) - Zhou, Benqing; Shen, Mingwu; Bányai, István; Shi, Xiangyang
Abstract : The internal spatial structures of PEGylated polyethylenimine-entrapped gold nanoparticles can be effectively analyzed via advanced NMR techniques. Abstract : NMR spectroscopy has been proven to be a useful method to characterize the spatial structure of polymer-protected nanoparticles (NPs). In the present study, polyethylenimine (PEI) partially modified with polyethylene glycol (PEG) was used as a template to form gold NPs (Au NPs) via either sodium borohydride reduction or PEI amine-mediated self-reduction of Au salt. The formed two types of PEGylated PEI-entrapped Au NPs (PEI-mPEG-Au NPs) were characterized by UV-vis spectroscopy and transmission electron microscopy, and their internal structures were characterized using NMR techniques. We show that the formed PEI-mPEG-Au NPs display a significant downfield shift in the proton signals of the innermost PEI methylene rather than the outer PEG methylene when compared to that of PEI-mPEG without Au NP entrapment. This result indicates that a strong interaction exists between the Au NPs and the innermost PEI, suggesting that the Au NPs are entrapped within individual PEI-mPEG instead of being stabilized by the surface PEG chains. In addition, the NMR diffusion coefficients of PEI (or PEG) in the PEI-mPEG-Au NPs are much higher than that of PEI-mPEG (without Au NPs), further demonstrating the effective Au NP entrapment. The present study provides a new physical insight into the internal spatial structure of polymer-protected Au NPs disclosed by NMR techniques, which may be used for structural characterization of other NP/polymer nanocomposites.